The constitutional paradigm of civil procedure. Theoretical bases - Delgado Suárez, Christian (2024)
This essay offers a feasible and verifiable theoretical basis for affirming what is called the fourth procedural paradigm, corresponding to the constitutional perspective of the civil procedure or the constitutionalization of it, as an overcoming of its previous classical and instrumentalist stages. To this end, through the interdisciplinary method, the research uses constitutional law, legal interpretation and procedural law to reshape the theoretical bases of the civil process and give it a constitutionalized value through the recognition of fundamental procedural rights as directly applicable norms containing optimization mandates. If it is a question of constitutionalizing the civil procedure, the essay, then, does not only seek the safe passage through the account of the so-called procedural guarantees. On the contrary, the functional or utility method applied to the same imposes that the contribution is to recognize the judge of the Constitutional State the duty of judicial protection even of the same fundamental procedural rights in the face of the defect or absence of rules that should implement and densify the principle of effective jurisdictional protection. This will make it possible to deconstruct and reconstruct concepts such as the fundamental right to effective judicial protection and the right of action, removing from them the slogan of mere guarantees that allow access to jurisdiction, to give them the character of optimization mandates directly executed by judges. It is, then, about the protection of the procedure, within the procedure, by the judge.